Aerogels with shape memory ability: Are they practical? —A mini-review. (5th October 2022) - Xiao, Xueliang; Panahi-Sarmad, Mahyar; Xu, Runxin; Wang, Ao; Cao, Shaojie; Zhang, Kanglei; Kamkar, Milad; Noroozi, Mina
Graphical abstract: Abstract: Aerogels are brand-new engineering porous materials, generated in abundance at the beginning of the 21st century. The promising features in conventional aerogels, such as extremely low thermal conductivity and high surface area, have led to their production at the commercial level for different applications such as thermal insulation. However, these lightweight materials frequently suffer from poor mechanical characteristics, limiting their utilization in advanced applications such as shape-memory actuators. Consequently, they should pass an upgrading stage to take themselves steps forward in the advanced world called smart materials. The pivotal point in advancing the shape-changing of such sensitive materials is to adjust their structure, from nano- to micro-level. This can be achieved by controlling aerogels' nanoscale building block interactions and the precise optimization of their composition and processing conditions, hence bestowing distinct capabilities on them. This review provides an overview of the results reported in the literature on the structural features and properties of aerogels as well as their shape memory applications, divided into three categories: (I) synthesized- based (II) bio-based, and (III) carbon-based aerogels. This review helps readers to discover aerogel trends and recognize their potential applications. The current paper also raises several fundamental obscure questions yet to be answered, triggering researchers to further explore this area, broadening the horizon of shape-memory lightweight materials.